2010
DOI: 10.1080/17451001003660301
|View full text |Cite
|
Sign up to set email alerts
|

Molluscan assemblages in littoral soft bottoms of the Alboran Sea (Western Mediterranean Sea)

Abstract: Table S1. List of the mollusc species collected in the survey between Cabopino and Calaburras, Málaga province, Spain. T1: transect off Torre de Calahonda; T2: transect off Torre Pesetas, T3: transect west of the river "Cala del Moral"; T4: transect west of "Cabezo del Fraile". The numbers given for each sampling point are the total live collected specimens for all replicates and all seasonal sampling campaigns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 18 publications
3
32
2
Order By: Relevance
“…Structurally complex environments increase species diversity by providing more niches and different ways of exploiting environmental resources (Kerr & Packer, 1997;Gingold et al, 2010), commonly referred as the "habitat heterogeneity hypothesis" (MacArthur & Wilson, 1967). The influence of heterogeneous habitats on the increase of local biodiversity has been indicated in other Mediterranean areas, such as the Alboran Sea (Urra et al, 2011(Urra et al, , 2013a.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Structurally complex environments increase species diversity by providing more niches and different ways of exploiting environmental resources (Kerr & Packer, 1997;Gingold et al, 2010), commonly referred as the "habitat heterogeneity hypothesis" (MacArthur & Wilson, 1967). The influence of heterogeneous habitats on the increase of local biodiversity has been indicated in other Mediterranean areas, such as the Alboran Sea (Urra et al, 2011(Urra et al, , 2013a.…”
Section: Discussionmentioning
confidence: 99%
“…Three replicates per station and month were generally taken, except in May and July 2009 at 10-15 m, with a total of 65 faunistic samples. This methodology has already been used successfully in studies of soft bottom molluscan assemblages (Rueda & Salas, 2003b;Urra et al, 2011). In the laboratory, faunistic samples were sieved over mesh sizes down to 0.5 mm, then stored in 70% ethanol.…”
Section: Faunistic Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, some of the Canonical Correspondence Analyses (CCA) showed that temperature and depth, as well as certain sediment-related variables, are important for explaining the distribution of mollusc assemblages, as observed in littoral studies of molluscs and decapods carried out in the northern Alboran Sea (García Muñoz et al, 2008;Urra et al, 2011). Temperature always correlated with axis I of the CCA, and sometimes less dispersion of slope samples was detected along this axis which could be related to the thermally stable environment below 200 m in the Mediterranean Sea (Hopkins, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, molluscs have been suggested, among other faunal groups, as proxies for assessing impacts or anthropogenic stress on total macrofaunal assemblages (Olsgard & Somerfield, 2000;Mendes et al, 2007). Studies of molluscan assemblages in the northern Alboran Sea have mainly been carried out in the infralittoral zone (soft bottoms: Urra et al, 2011;seagrass meadows: Rueda et al, 2008seagrass meadows: Rueda et al, , 2009Urra et al, 2013;rocky bottoms: Urra et al, 2012), with limited information on certain groups/species (Salas, 1996;González & Sánchez, 2002) and assemblages of the circalittoral and bathyal zone (Gofas et al, 2014a;Rueda et al, 2015). Therefore, the aims of the present study are to: (1) characterise the composition and structure of molluscan assemblages of circalittoral and bathyal sedimentary bottoms in the northern Alboran Sea using otter-trawl fishing gear, based on species analyses according to their lifestyle (i.e., demersal or benthic species) and different classes (i.e., bivalves, gastropods, and cephalopods); (2) analyse the spatial distribution patterns of these assemblages; and (3) discover which environmental variables relate to the structure and distribution of the molluscan assemblages.…”
Section: Introductionmentioning
confidence: 99%